The size distribution of profits from innovation - Frederic Michael Scherer (Zentrum für Europäische Wirtschaftsforschung (ZEW); ZBW – Leibniz Information Centre for Economics, 1996)
The research reported in this paper seeks to determine how skewed the distribution of profits from technological innovation is
Keywords: O31; 330; i.e.; whether it conforms most closely to the Paretian; log normal; or some other distribution. The question is important; because high skewness makes it difficult to pursue risk-hedging portfolio strategies. This paper examines data from several sources